Bounty Trough, seismic profile AWI-20110008 - Gabriele Uenzelmann-Neben (PANGAEA, 2023)
Processed data (SEGD) of seismic reflection profile AWI-2011008 collected during project SOPATRA with RV Sonne cruise SO213 in 2011. Migrated data collected with 3000 m digital streamer, 4 GI-guns were used as seismic source every 25 m. See cruise report of SO213 and readme file 20110008_segd_info for further details on acquisition parameters.